Claims vs. practicalities: lessons about using learning outcomes - Allais, Stephanie (My University, 2012)
The idea of learning outcomes seems to increasingly dominate education policy internationally. Many claims are made about what they can achieve, for example, in enabling comparison of qualifications across countries, improving the recognition of prior learning and improving educational quality. The claims made for the role of learning outcomes rest on the assumption that outcomes can be transparent, or that they can capture or represent the essence of what a learning programme or qualification represents. But in practice, either learning outcomes are open to dramatically different interpretations, or they derive their meaning from being embedded in a curriculum. In both instances, learning outcomes cannot play the roles that are claimed for them. I draw on insights from South Africa, where learning outcomes were a major part of curriculum and education policy reform. I suggest that outcomes cannot disclose meaning within or across disciplinary or practice boundaries. They did not enable the essence of a programme to be understood similarly enough by different stakeholders and they did not facilitate judgements about the nature and quality of education and training programmes. Learning outcomes do not carry sufficient meaning, if they are not embedded in knowledge within a curriculum or learning programme. But if they are thus embedded, they cannot play the roles claimed for them in assisting judgements to be made across curricula and learning programmes. The notion of transparency (or even, a more moderate notion of sufficient transparency) which proved unrealisable in practice is the basis of nearly all the claims made about what learning outcomes can achieve. In addition, the South African experiences demonstrated how outcomes-based approaches can distort education and training programmes, and lead to practical complexities, which are a direct consequence of the need for transparency, and its impossibility, and not (although this was probably also the case) the product of ‘poor implementation’ in South Africa.
Keywords: Outcomes-based education; Standards; National qualifications frameworks